The impact of the flexible forms of employment on pension risk - Benio, Marek (Journal of Public Governance, 2012)
The dynamic changes in the labour market in the first decade of the century have led to an increase in the number of people employed on the basis of civil law contracts and other flexible forms of employment. The revenues from these contracts are excluded from the contribution assessment basis, including old age pension insurance. As a result, an increasing number of people receiving income and participating in the labour market may be socially excluded in their old age due to low pension assets. This article does not examine the social scale of the phenomenon. Instead, analyzing legal documents and using microsimulation of old age income security based on risk biographies, it aims at explaining the impact of flexible employment on income security in old age. The analysis of the current mandatorysocial insurance coverage leads to the conclusion that flexible forms of employment may cause an increase in negative economic and social effects of the old age risk. It does not provide a social safety net. In their conclusion, the author suggests some legal changes.